(untitled) (NAU Journal of Library and Information Science, 2025)
Regardless of gender, research productivity is paramount for career progression and prestige of academic throughout universities in the world, however, observations showed that research productivity of female academic staff in Nigerian universities is undesirably low, which is due to many reasons. This study investigated the use of academic social networking sites and research productivity of female academic staff in public universities in South-West Nigeria. Survey research design of correlative type was adopted. 1785 female academic staff in the selected universities in South-West, Nigeria comprised the population of the study. Stratified random sampling technique was used to select 536 female academic staff in the selected universities. Out of 536 copies of questionnaire distributed, 413 copies were returned. Data collected were analysed using descriptive statistics of frequency count and percentages, mean and standard deviation, while Pearson Product Moment Correlation was used to test the three hypotheses. It was found that the level of use of academic social networking sites among female academics for research productivity was moderate (= 3.61) while research productivity of female academic staff is low (= 3.15). The major purposes of use of academic social networking sites for research productivity are searching of topics/ideas for thesis, conference papers, articles 371(89.8%) and links to publish their research 344(83.3%). There is a negative relationship between use of academic social network and research productivity (r = -0.212; p = 0.000). The study among other things recommended that female academic staff should be trained by the management of the universities to improve research productivity.